From spectral measurement to softening trajectory prediction: Integrating spatially resolved spectroscopy with kinetic modeling in Kiwifruit - Xuejian Zhou; Bin Li; Tetsuya Inagaki; Satoru Tsuchikawa; Te Ma (Postharvest Biology and Technology, 2026)

Integrated in-line transmission NIR monitoring and PLSR-based composition prediction for starch-based 3D food printing - Shaoyang Gao; Tetsuya Inagaki; Hao Jiang; Satoru Tsuchikawa; Te Ma (Food Chemistry, 2026)

Non-destructive diagnostics and early-warning systems for Penicillium rot in fresh produce: A review of emerging technologies - Wenpeng Ma; Te Ma; Dongchao Ji; Satoru Tsuchikawa (Trends in Food Science & Technology, 2026)

Plasma-activated water for sustainable postharvest preservation of fruits and vegetables: mechanistic insights into physiological regulation and stress priming - Teng Zhang; Tao Yang; Satoru Tsuchikawa; Tetsuya Inagaki; Te Ma; Hao Jiang (Food Research International, 2026)

Lysozyme as a protein-based carrier for bioactives: advances in delivery systems and gut environment interactions - Te Yu; Yuzhong Zheng; Yongping Huang; Yuan Ma; Grażyna Neunert; Jie Cao; Xing Fu (Trends in Food Science & Technology, 2026)

A Method for Calculating the Shortest Time Path for the Evacuation and Transfer of People at Risk of Flooding - Wei Ge; Heqiang Sun; Yutie Jiao; Laihong Jing; Yadong Zhang; Meimei Wu; Te Wang; Hua Zhang; Jianyou Wang; Yupan Qin; Fuheng Ma; Pieter van Gelder (Water Resources Management, 2026)

A digital microfluidics-based single-cell ddPCR platform for high-throughput gene copy number analysis applied to single cultured cells - Yicheng Sun; Jiancong Liang; Hui Li; Yechen Fan; Te Peng; Siyi Hu; Yuan Gao; Wenli Zhao; Ling Jiang; Khadija Urooj; Hanbin Ma; Mude Shi; et al. (Analytica Chimica Acta, 2026)

Precursor engineering via multifunctional additive for modulating perovskite crystallization and interface passivation enabled high-performance perovskite solar cells over 26% - Zhenye Liang; Chen Tian; Zhenhuang Su; Te Ji; Zhengwu Liu; Kunming Hou; Yulin Qin; Lianjie Ma; Junxiang Chen; Lingling Guo; Luozhen Jiang; Meng Du; et al. (Chemical Engineering Journal, 2026)

A field-deployable spectroscopic approach for optimizing kiwifruit harvest timing and postharvest quality management - Te Ma; Tetsuya Inagaki; Satoru Tsuchikawa; Hao Jiang (Postharvest Biology and Technology, 2026)

Correction to: Enhancing triterpenoids production in Ganoderma multipileum submerged cultures using caffeine as a P450 inducer and limonene as a precursor - Te-Wei Ma; Yu-Huan Chang (World Journal of Microbiology and Biotechnology, 2025)

Enhancing triterpenoids production in Ganoderma multipileum submerged cultures using caffeine as a P450 inducer and limonene as a precursor - Te-Wei Ma; Yu-Huan Chang (World Journal of Microbiology and Biotechnology, 2025)

Improvement of the YOLO Series for Detecting Tower Cranes Based on High-Resolution Remote Sensing Imagery - Tongyu Wu; Te Sha; Xiaojun Yao; Jiayu Hu; Yuxin Ma; Juan Zhang (Journal of Geovisualization and Spatial Analysis, 2025)

Design and development of a portable Vis-NIR spatially resolved spectroscopic device for nondestructive and rapid evaluation of growth stress in standing trees - Te Ma; Hiroyuki Yamamoto; Takusu Kajimura; Tetsuya Inagaki; Satoru Tsuchikawa (Computers and Electronics in Agriculture, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Intelligent monitoring of post-processing characteristics in 3D-printed food products: A focus on fermentation process of starch-gluten mixture using NIR and multivariate analysis - Qian Jiang; Yanru Bao; Te Ma; Satoru Tsuchikawa; Tetsuya Inagaki; Han Wang; Hao Jiang (Journal of Food Engineering, 2025)

Development of a time-resolved laser-induced fluorescence fingerprinting method for detecting low-level adulteration in extra virgin olive oil - Te Ma; Hao Jiang; Satoru Tsuchikawa; Tetsuya Inagaki (Food Chemistry, 2025)

Enhanced detection of early bruises in apples using near-infrared hyperspectral imaging with geometrical influence correction for universal size adaptation - Bin Li; Te Ma; Tetsuya Inagaki; Satoru Tsuchikawa (Postharvest Biology and Technology, 2025)

Enhanced quantification of chlorophyll a and its degradation products in olive oil using time-resolved laser-induced fluorescence fingerprint analysis - Te Ma; Hao Jiang; Satoru Tsuchikawa; Tetsuya Inagaki (Food Chemistry, 2024)

Two swords combination: Smartphone-assisted ratiometric fluorescent and paper sensors for dual-mode detection of glyphosate in edible malt - Kai Deng; Haipeng Guo; Xueying Li; Te Li; Tingting Di; Runran Ma; Doudou Lei; Yining Zhang; Jiabo Wang; Weijun Kong (Food Chemistry, 2024)

Three-dimensional visualization and detection of early bruise in apple based on near-infrared hyperspectral imaging coupled with geometrical influence correction - Bin Li; Te Ma; Leshang Bai; Tetsuya Inagaki; Hayato Seki; Satoru Tsuchikawa (Postharvest Biology and Technology, 2024)

Reliable sleep temperature regulation based on PMV model and dynamic thermal parameters - Zuoting Song; Yunlong Xia; Meirong Ma; Bin Deng; Te Miao; Qifeng Fan; Jilei Li (Building and Environment, 2024)

Elastoplastic damage behavior of quasi-brittle rocks considering crack closure evolution - Hongwei Li; Yuanming Lai; Mingyi Zhang; Yanyan Chen; Qinguo Ma; Te Liang; Xulong Gao (Computers and Geotechnics, 2024)

Application of Near-Infrared Spectroscopy to Forest and Wood Products - Satoru Tsuchikawa; Tetsuya Inagaki; Te Ma (Current Forestry Reports, 2023)

Mechanisms of damage to sperm structure in mice on the zinc-deficient diet - Bo Sun; Jing Ma; Junsheng Liu; Yuejia Li; Jiajie Bi; Liger Te; Xin Zuo; Shusong Wang (Journal of Trace Elements in Medicine and Biology, 2023)

A laboratory study of the phase ratio imagery method - Pei Ma; Hao Zhang; Yazhou Yang; Te Jiang; Daniel Britt; Menghua Zhu (Icarus, 2023)

Correction: Characteristics of land-subsidence evolution and soil deformation before and after the Water Diversion Project in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Yi Zhou; Fang Tian; Te Sha (Hydrogeology Journal, 2023)

Zinc-Deficient Diet Causes Imbalance in Zinc Homeostasis and Impaired Autophagy and Impairs Semen Quality in Mice - Bo Sun; Jing Ma; Liger Te; Xin Zuo; Junsheng Liu; Yuejia Li; Jiajie Bi; Shusong Wang (Biological Trace Element Research, 2023)

Development of a sensitivity-enhanced chlorophyll fluorescence lifetime spectroscopic method for nondestructive monitoring of fruit ripening and postharvest decay - Te Ma; Tetsuya Inagaki; Satoru Tsuchikawa (Postharvest Biology and Technology, 2023)

Assessment of a new multigeneration system based on geothermal plant and a linear Fresnel reflector-based solar unit: An effort to improve performance - Te Ma; Lan Lan; Mohammad Marefati (Process Safety and Environmental Protection, 2023)

Correlation between serum zinc and testosterone: A systematic review - Liger Te; Junsheng Liu; Jing Ma; Shusong Wang (Journal of Trace Elements in Medicine and Biology, 2023)

Visible and near-infrared reflectance spectra of igneous rocks and their powders - Yan Zhuang; Hao Zhang; Pei Ma; Te Jiang; Yazhou Yang; Ralph E. Milliken; Weibiao Hsu (Icarus, 2023)

Characteristics of land-subsidence evolution and soil deformation before and after the Water Diversion Project in Beijing, China - Kunchao Lei; Fengshan Ma; Beibei Chen; Yong Luo; Wenjun Cui; Yi Zhou; Fang Tian; Te Sha (Hydrogeology Journal, 2022)

Potential Plasticity of Artificial Feed Preference in Juvenile Pharaoh Cuttlefish (Sepia pharaonis) Through Progressive Training Programs - Chia-Huan Ma; Chih-Hung Lin; Yung-Cheng Chang; Hung-Tai Lee; Chyng-Hwa Liou; Te-Hua Hsu (Frontiers in Marine Science, 2022)
The cuttlefish is a commercially important marine species across the world; however, due to the lack of appropriate artificial feed, there is limited future aquaculture development of the cuttlefish. We proposed a novel process comprising (1) feed preference tests and (2) progressive training programs. Through this process, artificial diets can become more suitable for pharaoh cuttlefish ( Sepia pharaonis ). Feed preference tests (based on vision, touch, and smell) revealed that pharaoh cuttlefish preferred rod-shaped feed to flat rod-shaped or ball-shaped feed, moist feed over dry feed (DF), and DF with agar coating to DF without agar coating. Without olfactory training, some cuttlefish refused to eat artificial feed and eventually died. Through progressive training programs (3- and 6-week programs), a survival rate of >80% was achieved. Although the artificial diets examined in this study resulted in a lower conversion ratio for S. pharaonis than for fresh shrimp, available artificial feed can potentially be adopted for cuttlefish aquaculture through the use of our progressive training program.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Effects of drip irrigation on deep root distribution, rooting depth, and soil water profile of jujube in a semiarid region - Li-hui Ma; Xiao-li Liu; You-ke Wang; Pu-te Wu (Plant and Soil, 2013)

Spatial distribution of roots in a dense jujube plantation in the semiarid hilly region of the Chinese Loess Plateau - Li-hui Ma; Pu-te Wu; You-ke Wang (Plant and Soil, 2012)